ATM and Artemis promote homologous recombination of radiation-induced DNA double-strand breaks in G2 - Beucher, Andrea (Nature Publishing Group, 2009)
Homologous recombination (HR) and non-homologous end joining (NHEJ) represent distinct pathways for repairing DNA double-strand breaks (DSBs). Previous work implicated Artemis and ATM in an NHEJ-dependent process, which repairs a defined subset of radiation-induced DSBs in G1-phase. Here, we show that in G2, as in G1, NHEJ represents the major DSB-repair pathway whereas HR is only essential for repair of ∼15% of X- or γ-ray-induced DSBs. In addition to requiring the known HR proteins, Brca2, Rad51 and Rad54, repair of radiation-induced DSBs by HR in G2 also involves Artemis and ATM suggesting that they promote NHEJ during G1 but HR during G2. The dependency for ATM for repair is relieved by depleting KAP-1, providing evidence that HR in G2 repairs heterochromatin-associated DSBs. Although not core HR proteins, ATM and Artemis are required for efficient formation of single-stranded DNA and Rad51 foci at radiation-induced DSBs in G2 with Artemis function requiring its endonuclease activity. We suggest that Artemis endonuclease removes lesions or secondary structures, which inhibit end resection and preclude the completion of HR or NHEJ.